A Case of Delayed Right Ventricle Perforation following Permanent Pacemaker Insertion complicated with Sepsis - Shena, Tamanna Yasmin; Umme Kulsum Chy; Amina Sultana; Mohammad Omar Faruq (Bangladesh Critical Care Journal, 2024)
Bangladesh Crit Care J March 2024; 12 (1): 75-78 Abstract not available